How Energy Constraints Drive Firms’ Participation in the Global Value Chain? International Evidence - Nguyen, Thuy Thi Cam; Luong, Dat Van; Ngo, Hoang Thu; Doan, Thang Ngoc (International Journal of Energy Economics and Policy, 2025)
This study explores how energy constraints affect firms’ participation in global value chains (GVCs). Drawing on extensive plant-level data from the World Bank Enterprise Survey, covering the manufacturing sector in 119 countries from 2005 to 2022, the analysis reveals that energy constraints significantly hinder firms’ ability to engage in GVCs. This adverse effect is primarily driven by reduced productivity, increased energy expenses, and diminished investments in machinery. However, the impact is not uniform, varying by time periods, firm sizes, sectors, and regions. Smaller firms and those in energy-intensive industries are particularly vulnerable, while regional differences underscore the role of infrastructure quality and the effectiveness of energy policies. The robustness of the findings is verified using alternative measures and approaches that mitigate potential endogeneity concerns. These insights provide important policy implications aimed at enhancing firms’ participation in GVCs through targeted energy infrastructure and policy improvements.